SOSIALISASI STOP BULLYING, WUJUDKAN SEKOLAH RAMAH ANAK DI SDN KERTASANA2 KECAMATAN PAGELARAN - Setyanto Pramono, Aris; Safiulloh, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
A socialization activity with the theme "Stop Bullying, Create a Child-Friendly School" was held at SDN Kertasana 2 with the aim of increasing students' understanding of the negative impacts of bullying and fostering mutual respect in the school environment. This socialization was carried out through interactive counseling, educational video screenings, and group games that encourage cooperation and empathy among students. Through this activity, participants gained a better understanding of the forms of bullying, how to prevent it, and steps to take if they experience or witness bullying. Evaluation results showed an increase in student awareness of the importance of creating a safe, comfortable, and violence-free school. This activity is expected to be the first step in realizing a child-friendly school that supports optimal student growth and development.